Dynamic crushing behavior of multi-layered hybrid foam-filled composite graded lattice sandwich panels. Issue 27 (14th December 2022) - Yang, Jin-Shui; Chen, Si-Yuan; Liu, Xu-Chang; Lin, Zhuang; Yang, Li-Hong; Schröder, Kai-Uwe; Schmidt, Rüdiger
Abstract: The research and development of novel protective structures with excellent mechanical load-bearing and energy-absorbing characteristics are one of the current interests in aerospace, marine, and automobile industries. In this research, we fabricate foam-filled multi-layered hybrid composite graded lattice sandwich panels (MHCGLSPs) with different configurations and investigate their dynamic response characteristics experimentally and numerically. The influences of strain rate, relative density, filled foam, and graded arrangement on the crushing behavior of the present panels are depicted, and three main failure modes including core buckling (CB), facesheet breakage (FB), and polyurethane foam breakage (PB) are revealed. Furthermore, the numerical results obtained by finite element models based on the Hashin failure criterion and Johnson–Cook model are in good agreement with the experimental results. It is shown that all the present MHCGLSPs possess excellent energy absorption performance, and the non-graded specimens and gradually weaker specimens possess better ultimate load-bearing capacity under the premise of equal relative density, which can provide guideline for further studies on the novel multi-layered protective structures.